Developing an integrated theoretical model of young peoples' condom use in sub-Saharan Africa - Protogerou, C.; Hagger, Martin (John Wiley & Sons Ltd., 2016)
Objective: We aimed to develop an integrated theoretical model of the determinants of condom use in young people from sub-Saharan African (SSA) nations. Model development was informed by research predicting condom use in SSA nations adopting individual-level social-cognitive and socio-ecological theories, and guided by McMillan and Conner's (2007) framework of social-cognitive predictors of health. Method: We conducted a scoping review of research on social-cognitive and socio-ecological predictors of condom use in young people in SSA. The integrated model was developed based on the constructs from the review and guided by McMillan and Conner's framework to classify the constructs and isolate the processes by which the constructs impact condom use. Results: Included studies (N=45) utilised constructs from seven individual-level social-cognitive theories and included multiple socio-ecological variables as predictors of condom use. The integrated model included dispositions to act as a proximal determinant of condom use which mediated the effect of four categories of social-cognitive constructs on condom use: attitudes, control perceptions, norms, and self-representations. Socio-ecological factors were classified into four categories: relational, individual differences, societal/structural, and community and peer influences. Each had direct and indirect effects on condom use in the model, reflecting the non-conscious and conscious pathways to action, respectively. Conclusion: We expect our integrated model to provide an evidence- and theory-based guide to future research examining the antecedents of condom use in young people in SSA. We also anticipate it will assist in developing targets for interventions that will be effective in promoting condom use in this population.